Prevalence of hyperuricemia among patients undergoing hemodialysis: Approach to understanding the risk factors - Atbee, M.Y.N. Al; Hassan, I.E.; Mnahi, H.N.; Nassir, H.A.; Yahya, A.A.; Abdulbari, Z.M. (Ukrainian Journal of Nephrology and Dialysis, 2023)
Chronic Kidney Disease (CKD) is closely associated with hyperuricemia. Elevated urate levels and hyperuricemia are common in patients with impaired renal function. Kidney replacement therapies, such as hemodialysis and kidney transplantation, are conventional treatment strategies for end-stage kidney disease (ESKD). The present study aimed to determine the prevalence of hyperuricemia and investigate its correlation with demographic characteristics, clinical comorbidities, and biochemical parameters in patients undergoing hemodialysis. Method. In this retrospective study, we assessed the prevalence of hyperuricemia in 102 hemodialysis patients at the Nephrology and Dialysis Department of Basra Teaching Hospital in Basra, Iraq. We recorded demographic characteristics, such as age and gender, and examined whether there was any correlation with hyperuricemia. Additionally, we assessed the association of hyperuricemia with clinical comorbidities like diabetes and cardiovascular diseases in these patients. Clinical chemistry and electrolyte parameters were analyzed using a high-performance serum work area platform, COBAS C 111. Results. Among all the assessed biochemical parameters, magnesium showed a significant association with hyperuricemia in patients undergoing hemodialysis. We also found a statistically significant association between hyperuricemia and cardiovascular diseases in these patients. These findings underscore the significance of hyperuricemia as both a risk factor and a potential target for therapeutic interventions in managing these comorbidities. Conclusion. This study highlights the importance of monitoring uric acid levels in patients undergoing hemodialysis to gain a more comprehensive understanding of their health, from the cellular to the organ level.